TGase-induced WPI-GA microgels for stabilized HIPEs and encapsulation probiotics with enhanced thermal stability and gastrointestinal survival - Yin, Yaxin; Zou, Yingnan; Tan, Chin Ping; Li, Deyang; Zheng, Xiaojiao; Pan, Daodong; Tu, Maolin (Elsevier B.V., 2026)
Probiotics demonstrate significant efficacy in regulating gut microbiota and enhancing immune function. However, their sensitivity severely limited their application. This study employed transglutaminase (TGase) to enzymatically cross-link whey protein isolate (WPI) and Gum Arabic (GA), and prepared microgel particles. These were utilized as stabilizers in high internal phase emulsions (HIPEs) to encapsulate Lactobacillus reuteri DSM 17938 (L. reuteri). SDS-PAGE analyses confirmed that TGase-induced polymerization, showing the corresponding formation of high-molecular-weight polymers. This covalent cross-linking inherently altered the microgel structure, leading to significant functional modifications. Particle size and rheological results indicated that HIPEs exhibited excellent viscoelasticity and stability. By investigating the effects of WPI-GA concentration and oil volume fraction, it was found that L. reuteri encapsulated in HIPEs demonstrated outstanding thermal stability and resistance to simulated gastrointestinal digestion. After simulated gastric digestion, the viability of probiotics decreased from 7.6 to 3.0 Lg CFU/mL. The probiotics in the 4% microgel-stabilized HIPEs maintained a higher count of 5.1 Lg CFU/mL. These results show that protein-polysaccharide microgel-stabilized HIPEs can protect probiotics more effectively. The findings also provide useful guidance for developing stable probiotic delivery systems.